Corporate Pay-out Policy and Test of Life Cycle Theory; Evidence from Nepalese Commercial Banks - Dhungana, Ajaya; Devkota, Tej Prasad (NRB Economic Review, 2022)
Dividend policy of firm in theoretical finance is one of the most controversial issue, various theories of dividend policy try to explain the dividend behaviour of the firm. The dividend distributed by a firm to its shareholder is very different when it is viewed from the perspective of the company’s life cycle. If no regulation forces, then firms at initial stage have higher investment opportunities, so they retain all their earning and pay no dividend. The firms at maturity stage have less investment opportunities, slow pace of growth rate and lower cost of raising external capital, hence, mature firms retain less and pays higher dividend. Life cycle hypothesis suggests that firm increases their dividend with their maturity. This study investigates the dividend behaviour of Nepalese commercial banks, by using the ten years panel data for the period from 2010 to 2019. Using conventional proxies of life cycle, the result of the study consistently shows that Nepalese listed commercial bank follow dividend life cycle theory. The result also shows that larger firms pay higher dividend and dividend history has positive relation with next period dividend payment. The result is robust and such robustness check has been conducted by altering some of the proxies of the variables. The result of the study suggest that the regulators should not impose same dividend policy to the entire banking industry.